Antibiotic Potentiation of Natural Products: A Promising Target to Fight Pathogenic Bacteria - Sadeer, Nabeelah B.; Mahomoodally, Mohamad Fawzi (Current Drug Targets, 2021)
Pathogenic microorganisms should be considered as the number one foe of human, as witnessed by recent outbreaks of coronavirus disease (COVID-19) and with bacteria no longer sensitive to existing antibiotics. The resistance of pathogenic bacteria and deaths attributable to bacterial infections is increasing exponentially. Bacteria used different mechanisms to counterattack to existing antibiotics, namely (i) enzymatic inhibition, (ii) penicillin-binding protein modification, (iii) porin mutations, (iv) efflux pumps and (v) molecular modifications of antibiotic targets. Developing new antibiotics would be time-consuming to address such a situation, thus one of the promising approaches is by potentiating existing antibiotics. Plants used synergism to naturally defend and protect themselves from microbes. Using the same strategy, several studies have shown that the combinations of natural products and antibiotics could effectively prolong the lifespan of existing antibiotics and minimize the impact and emergence of antibiotic resistance. Combining essential oils constituents, namely uvaol, ferruginol, farnesol and carvacrol, with antibiotics, have proved to be efficient efflux pump inhibitors. Plant-derived compounds such as gallic acid and tannic acid are effective potentiators of various antibiotics, including novobiocin, chlorobiocin, coumermycin, fusidic acid, and rifampicin, resulting in a 4-fold increase in the potencies of these antibiotics. Several lines of research, as discussed in this review, have demonstrated the effectiveness of natural products in potentiating existing antibiotics. For this reason, the search for more efficient combinations should be an ongoing process with the aim to extend the life of the ones that we have and may preserve the life for the ones that are yet to come.
Keywords: Antibiotics